ISLAMISASI PENGETAHUAN ISMAIL RAJI AL-FARUQI DAN RELEVANSINYA DENGAN INTEGRALISME PENDIDIKAN - Nisok, Siti Roisadul (Universitas Nahdlatul Ulama Surakarta, 2024)
This research explores the concept of Islamization of Knowledge by Ismail Raji al-Faruqi and its implications for educational integralism. The focus of the research lies on analyzing al-Faruqi's thoughts in transforming knowledge through an Islamic lens, as well as how this view can be applied concretely in the context of education. This research outlines the concept of educational integralism as an attempt to integrate Islamic values in all dimensions of education. Through a critical approach, this research evaluates the relevance of al-Faruqi's concept of Islamization of Knowledge in achieving the goal of educational integralism. The results of the study are expected to contribute to a deeper understanding of the potential and challenges in adopting al-Faruqi's principles in an effort to improve the quality of education that is more consistent with Islamic values.